The carbon footprints of home and in-center peritoneal dialysis in China - Chen, Mindong; Zhou, Rong; Du, Chongbo; Meng, Fulei; Wang, Yanli; Wu, Liping; Wang, Fang; Xu, Yahong; Yang, Xiufen (International urology and nephrology, 2017)
Objective The provision of healthcare itself is associated with abundant greenhouse gas (GHG) emissions. This study aims to determine the carbon footprints of peritoneal dialysis (PD) with the different modalities and treatment regimes. Methods A total of 68 subjects performed with PD treatment were enrolled in this study. Emissions factors were applied to data that were collected for energy consumption, travel, and procurement. Results The carbon footprints generated by the provision of PD treatment for the individual patient were calculated and normalized to a 2-l PD dialysate volume. The fixed emissions were higher in patients who received PD therapy in center than at home, mostly attributing to the consumption of electricity. Conversely, PD treatment performed in center yielded less variable emissions than that of at home, which resulted from reduced constituent percentage of waste disposal and transportation. Collectively, packaging consumption mostly contributed to the total carbon footprints of PD. Conclusion This study for the first time demonstrates the delivery of PD is associated with considerable GHG emissions, which is mainly attributed to packaging materials, transportation, electricity, and waste disposal. These results suggest that carbon reduction strategies focusing on packaging consumption in PD treatment are likely to yield the greatest benefits.